Therapeutic stem cell‐derived alveolar‐like macrophages display bactericidal effects and resolve Pseudomonas aeruginosa‐induced lung injury. Issue 10 (20th April 2022) - Bouch, Sheena; Litvack, Michael L.; Litman, Kymberly; Luo, Lisha; Post, Alex; Williston, Emma; Park, Amber J.; Roach, Elyse J.; Berezuk, Alison M.; Khursigara, Cezar M.; Post, Martin
Abstract: Bacterial lung infections lead to greater than 4 million deaths per year with antibiotic treatments driving an increase in antibiotic resistance and a need to establish new therapeutic approaches. Recently, we have generated mouse and rat stem cell‐derived alveolar‐like macrophages (ALMs), which like primary alveolar macrophages (1'AMs), phagocytose bacteria and promote airway repair. Our aim was to further characterize ALMs and determine their bactericidal capabilities. The characterization of ALMs showed that they share known 1'AM cell surface markers, but unlike 1'AMs are highly proliferative in vitro . ALMs effectively phagocytose and kill laboratory strains of P . aeruginosa ( P . A .), E . coli ( E . C .) and S. aureus, and clinical strains of P . A . In vivo, ALMs remain viable, adapt additional features of native 1'AMs, but proliferation is reduced. Mouse ALMs phagocytose P . A . and E . C . and rat ALMs phagocytose and kill P . A . within the lung 24 h post‐instillation. In a pre‐clinical model of P . A .‐induced lung injury, rat ALM administration mitigated weight loss and resolved lung injury observed seven days post‐instillation. Collectively, ALMs attenuate pulmonary bacterial infections and promote airway repair. ALMs could be utilized as an alternative or adjuvant therapy where current treatments are ineffective against antibiotic‐resistant bacteria or to enhance routine antibiotic delivery.